Forestry and Forest Products Statistics in India - Sangal, P. M. (Indian Forester, 1972)
An examination of the available statistics relating to the forests, forest based industries and marketing of forest products in the country has been undertaken in the context of the use to which such statistics are to be put. This examination has revealed several limitations of the present system of collection of the statistical information. Possible remedial measures suggested include declaring the Heads of State Forest Departments as Statistical Authority in respect of the forest areas and forest based industries located within their territorial jurisdiction, setting up of an organisation at central and state levels to deal with marketing of forest products, centralisation of collection and compilation of statistical information and taking up special enduse surveys, drain surveys etc.